(untitled) (Research, Society and Development, 2022)
Objective: To discuss the prejudice and the limitation that still exists by health professionals in primary care in the face of STI with LGBT people and place the nurse as the main instrument from diagnosis to treatment. Methodology: The search was based on the relationship between the contents of these themes and the guiding question of the study, taking a cut within the last six years. After an even more careful analysis, to identify and seek evidence that dialogues with the object of this study, a final sample of 12 articles was obtained from a total of 54 findings, resulting in an integrative review. Results and Discussion: To enable a better study and understanding of the articles, a synoptic table was elaborated, which presented the synthesis of all articles that were inserted in the research and that represent the basis for the elaboration of the discussion on the attribution of nurses in primary care in relation to STI in the LGBT population. Conclusion: Health professionals recognize the vulnerability of the LGBT population and that there is a need for knowledge on the subject. There is a need for a greater search for knowledge, training and resources to offer better assistance.